2013
DOI: 10.1371/journal.pone.0059631
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Regulation of Trypanosoma congolense-Induced Nitric Oxide Production in Macrophages

Abstract: BALB/c mice are highly susceptible while C57BL/6 mice are relatively resistant to experimental Trypanosoma congolense infection. Several reports show that an early interferon-gamma (IFN-γ) response in infected mice is critically important for resistance via the activation of macrophages and production of nitric oxide (NO). NO is a pivotal effector molecule and possesses both cytostatic and cytolytic properties for the parasite. However, the molecular mechanisms leading to T. congolense (TC)-induced NO release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…In addition to the production of pro-inflammatory cytokines, macrophages also produce nitric oxide, which plays a critical role in resistance against African trypanosomes via its cytostatic and cytotoxic effects ( 93 95 ). This is not surprising, given that the intracellular signaling pathways that result in the production of pro-inflammatory cytokines also lead to the activation of the iNOS gene and subsequent production of nitric oxide ( 96 ). Recently, we showed that in an IFN-γ-enriched environment, T. congolense -treated immortalized macrophages and BMDMs from the relatively resistant and highly susceptible mice show differential phosphorylation of MAPKs and STATs, suggesting that African trypanosomes induce differential signaling events in macrophages from different strains of mice in vitro ( 96 ).…”
Section: Trypanosome-induced Signaling In Relatively Resistant Versusmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to the production of pro-inflammatory cytokines, macrophages also produce nitric oxide, which plays a critical role in resistance against African trypanosomes via its cytostatic and cytotoxic effects ( 93 95 ). This is not surprising, given that the intracellular signaling pathways that result in the production of pro-inflammatory cytokines also lead to the activation of the iNOS gene and subsequent production of nitric oxide ( 96 ). Recently, we showed that in an IFN-γ-enriched environment, T. congolense -treated immortalized macrophages and BMDMs from the relatively resistant and highly susceptible mice show differential phosphorylation of MAPKs and STATs, suggesting that African trypanosomes induce differential signaling events in macrophages from different strains of mice in vitro ( 96 ).…”
Section: Trypanosome-induced Signaling In Relatively Resistant Versusmentioning
confidence: 99%
“…This is not surprising, given that the intracellular signaling pathways that result in the production of pro-inflammatory cytokines also lead to the activation of the iNOS gene and subsequent production of nitric oxide ( 96 ). Recently, we showed that in an IFN-γ-enriched environment, T. congolense -treated immortalized macrophages and BMDMs from the relatively resistant and highly susceptible mice show differential phosphorylation of MAPKs and STATs, suggesting that African trypanosomes induce differential signaling events in macrophages from different strains of mice in vitro ( 96 ). In addition to differential MAPK and STAT phosphorylation, T. congolense induces significantly higher levels of NO production in IFN-γ-primed immortalized macrophages and BMDMs the relatively resistant than from highly susceptible mice ( 96 ).…”
Section: Trypanosome-induced Signaling In Relatively Resistant Versusmentioning
confidence: 99%
See 2 more Smart Citations
“…From the invasive step and the ascending phase of parasitemia in the mammalian host ( Figure 2), proliferating parasites face innate resistance mechanisms mainly relying on type I interferon (IFN), NO, and tumor necrosis factor (TNF) released by M1-type myeloid cells [39][40][41][42][43].…”
Section: M1-type Myeloid Cells Contribute To Resistance In the Mammalmentioning
confidence: 99%